Development of Pharmacist Independent Prescribing Clinics to Treat Opioid Analgesic Dependence in NHS Lanarkshire - Duncan Hill; Elizabeth Marr; Clair Smith (MDPI AG, 2019)
There has been an increase in opioid analgesic prescribing in general practice (GP). This is causing some concern around this contributing to dependency. NHS Lanarkshire have attempted to reduce the prescribing from GP surgeries through the development of specialised Pharmacist Independent Prescriber clinics being delivered from the practices. This article looks at the development of these services with pharmacist independent prescribers and the results from developing the services. The article aims to provide advice and recommendations for the development of other services and strategies to minimise the risks associated with Opioid Analgesic Dependence for patients.